Rancang Bangun Aplikasi Analisis Kepuasan Pelanggan Pada Lazizaa Chicken And Pizza Cabang Kusuma Bangsa Surabaya - Hantoro, Yomanda Maulana; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
So far there is no kusioner to know customer satisfaction, so that every complaint is delivered orally. Those complaints are Accepted by management Lazizaa Chicken And Pizza for example less complete Facilities, cleanliness, waiting time in serving some menu such as long time pizza, facilities to wait for inadequate order, and others. The problem is when the complaint is delivered verbally to the employee Lazizaa Chicken And Pizza, often the employee who received the complaint forgot to convey to the management because the complaint is not written and undocumented. Therefore in this study, made a Design Build Customer Satisfaction Application At Lazizaa Chicken and Pizza Branch Kusuma Nation Surabaya, so it can help to know the level of customer satisfaction. This application is web based because it can simplify its implementation and also can be accessed on all platforms that can use web browser. Based on the experiments on the application, it can be accessed easily by IT staff to manage the questionnaire data, displaying the results of customer analysis in the form of reports in the form of graphs and tables so that owners Lazizaa Chicken And Pizza can view reports of analysis results through web-based applications. For development advice is expected to be integrated with all the other branches Lazizaa.